عمارة أهرامات وادي الملوك في شمال السودان - خضرة, فؤاد (Latakia University Journal -Engineering Sciences Series, 2019)
يسلط هذا البحث الضوء على أحد مظاهر الحضارة السودانية إنها أهرامات السودان. فبالرغم من أهميتها وتمتعها بالكثير من المزايا لم تنل هذه الأهرامات نصيباً وافراً من الشهرة بقدر ما نالته نظيراتها في مصر. كما تقدم الدراسة الآتية شرحاً عن أهم مواقع هذه الأهرامات، وكذلك أنواعها وتصنيفاتها ومراحل تطورها. مستعرضاً مدى التأثر المزدوج والمتبادل بين حضارة كل من شمال النيل وجنوبه . ومن خلال مقارنة بين أهرمات كل من مصر والسودان يبين البحث عبر مجموعة من الدلائل بأنهما لم تكونا نسختين متطابقتين تماماً, بل تفرد كل منهما بهويته ومميزاته التي جعلت هذه المشيدات من أعظم ما بناه الإنسان عبر العصور سواء من ناحية الشكل الهندسي وتطوره أو أسلوب البناء أو حتى بالاعتماد على مواد بناء محلية امتزجت مع معتقدات دينية وروحية لتنتج فناً معمارياً يرتقي إلى درجة الخلود, هذه الدرجة التي لم تأت من فراغ إنما من موقع وعاصمة لأول مملكة في العالم وفقاً لما يهدف ويشير البحث إليه من خلال بيان آثارها وحضارتها . This study throws the light on one of the phenomena of the Sudanese civilization: The Pyramids of Sudan. In spite of their importance and many characteristics, these Pyramids did not gain as much fame as that gained by their pars, the Pyramids of Egypt. The following study provides an explanation of the most important sites of these Pyramids, their kind, classifications and their stages of development. It discusses the degree of double and mutual influence of each of the civilizations of the north and south of the Nile on the other. Through a comparison of the Pyramids of Sudan with those of Egypt, the study shows, through a set of guidelines, that they were not identical copies, one of the other, but every set has its identity and characteristics that made these monuments ones of the greatest that Man has ever constructed over the ages , whether for their geometrical shapes, development or the style of building, or even the use of local building materials mixed with religious and spiritual beliefs, to form an architectural art that rises to the degree of immortality.